Political background of the end of the Greek bailout programme - Denis Zelikson (Научно-аналитический вестник Института Европы РАН, 2019)
In 2015 SYRIZA described the end of the bailout as one of the main goals of its public administration. Greece has been implementing tough structural reforms from 2010 to 2018 to receive low-costs financing. In order to gain support from the Greek citizens in August 2018 Alexis Tsipras proclaimed the completion of the third memorandum as the political success as well as the end of crisis. However, the fictional defeat of technocrats from Brussels has not dispensed Greece from ongoing structural reforms, but restricted the country’s access to low-costs financing. Moreover, SYRIZA itself has not received any political benefits as well. The third bailout programme has eventually helped to stabilize the Greek debt, unemployment rate and primary balance. However, the fourth memorandum may occur due to the weakness of the Greek economy